An appraisal of the Dietary Department of the Philippine General Hospital, (1952-1966) - Domingo, Flora M. 1926-; De la Paz, Sylvia Y. (1967)
This study was undertaken to appraise the various aspects of operation of the Dietary Department of the Philippine General Hospital from the point of view of nine dietitians currently employed by the hospital as well as four other dietitians who have resigned but served at lest two years for the past five years. The writer is the tenth staff member who did not answer the check sheet since she analyzed the data based on her fourteen years of experience as a dietitian in the Philippine General Hospital and readings of pertinent literature. The check sheet used in this study was patterned after the list prepared by a special committee of the American Dietetic Association. It was divided into five series to avoid taxing the respondents. The major areas of operation evaluated were organization, personnel policies, responsibilities, facilities, education, appraisal and research. The study also covered areas which needed concentration in the next year and within the next five years. The responses revealed that there is a need to clarify, review, and evaluate the functions and objectives of the Department as well as the line and functional responsibilities of all personnel. Lack of personnel may be partly solved by hiring two food service supervisors and a clerk. Personnel policies are governed by the Civil Service Act of 1959 and the rules of the Wage and Position Classification Office or WAPCO. Promotion is based on merit and/or tenure. Job descriptions should be regularly reviewed and job specifications available for all positions. Quality food service is hampered by limited budget, large number to feed, lack of personnel, inadequate and poorly maintained equipment, faulty physical layout, and poor lightning and ventilation. There has to be an effective line of communication between the administrator and dietitians for a more realistic budget. An up-to-date diet manual is in order. Facilities need to be increased and improved. Standards of sanitation should be established and maintained. Safety programs must be held regularly. Training and continuous education programs should be afforded all dietary employees. Appraisal and research may be done in any phase of dietetics if and when staff and resources are available. To date, there are no reported studies on the evaluation of dietary departments of Philippine hospitals. The common yardstick is food acceptance of patients and personnel. It is hoped that this report may spark similar studies by dietary units of both public and private hospitals. Lastly, with this study as a formal start, a periodic evaluation of the Dietary Department - at least every five years- is hereby recommended, to determine whether or not goals have been reached.
Thesis (M.S.)--University of the Philippines, Diliman.